CONDITIONAL DEATH PENALTY SENTENCING IN THE NEW INDONESIAN CRIMINAL CODE: A NON-DEROGABLE RIGHTS PERSPECTIVE - Susanto, Susanto; Efendi, Dr. Jonaedi; Suroso, Dr. Imam (jfpublisher, 2025)
The conditional death penalty under Indonesia’s Law No. 1 of 2023 on the Criminal Code (KUHP) represents a critical reform in balancing human rights protection and state authority in criminal justice. This study examines the legal and philosophical foundations of the conditional death sentence through the perspective of non-derogable rights—particularly the right to life as an inviolable human right. Using a normative juridical methodology combining statutory and conceptual approaches, this research analyzes the new KUHP’s regulatory framework, especially Article 100, which introduces a ten-year probationary period allowing sentence conversion to life imprisonment. The findings demonstrate that conditional death sentencing serves as a middle ground between abolitionist and retentionist camps in Indonesian legal discourse. It reflects a progressive penal policy aligning with constitutional guarantees in Article 28I(1) of the 1945 Constitution and international human rights instruments, such as the International Covenant on Civil and Political Rights (ICCPR). The study concludes that conditional death sentencing embodies a transitional penal paradigm—anchored in restorative and humanistic values—reaffirming the state’s dual obligation to uphold the right to life while ensuring collective security and justice.